2006
DOI: 10.1021/jf052979j
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus plantarum and Pediococcus pentosaceus Starter Cultures as a Tool for Microflora Management in Malting and for Enhancement of Malt Processability

Abstract: Lactobacillus plantarum VTT E-78076 (E76) and Pediococcus pentosaceus VTT E-90390 (E390) starter cultures were added to the steeping water of normal malting barley in order to balance the microbial community and to enhance malt processability. In this study, we also investigated the effects of lactic acid-acidified MRS-spent medium (MRS-LA) on malting performance. Malting trials with five different two-row barley varieties were carried out in 25 kg pilot scale. The starter cultures promoted yeast growth during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 52 publications
4
30
0
Order By: Relevance
“…Suppression of the bacterial community promoted yeast growth. A similar trend was observed in our previous study with lactic acid starter cultures 31 . Addition of starter cultures into the steeping water decreased the growth of gram-negative bacteria but increased yeast growth.…”
Section: Discussionsupporting
confidence: 91%
“…Suppression of the bacterial community promoted yeast growth. A similar trend was observed in our previous study with lactic acid starter cultures 31 . Addition of starter cultures into the steeping water decreased the growth of gram-negative bacteria but increased yeast growth.…”
Section: Discussionsupporting
confidence: 91%
“…It has been shown that a speciWc microbial community develops in each malting plant [51,52]. Furthermore, the yeast community present in the malting process depends on the initial population of barley, interactions between the diVerent microbial groups, process conditions such as temperature and aeration, and the use of antimicrobial treatments such as starter cultures [25,43,49,52].…”
Section: Resultsmentioning
confidence: 99%
“…Some yeasts normally associated with malting have shown strong antagonistic activity and have been applied as natural biocontrol agents to restrict the growth of harmful fungi [6,17]. Our previous studies with lactic acid starter cultures revealed that the addition of lactic acid bacteria (LAB) into the steeping activated the indigenous yeast community and enhanced the production of microbial -glucanase and xylanase in the malting process 43]. However, the source of these microbial enzymes was unknown, and we suggested that enhanced growth of the yeast community could partly explain the increased enzyme activities.…”
Section: Introductionmentioning
confidence: 99%
“…Yeast and lactic acid bacteria often occurring together in plant-based bioprocesses and synergistic interactions between these two groups are utilized in many cereal fermentations [4]. We have previously shown that the addition of lactic acid bacteria (LAB) into malting activated the indigenous yeast community and enhanced production of microbial -glucanase and xylanase in the malting process [34]. Combining antagonistic yeast with lactic acid bacteria might further enhance the usefulness of starter technology in complex bioprocesses such as malting.…”
Section: Introductionmentioning
confidence: 99%